ChemInform Abstract: Room‐Temperature Hydrodehalogenation of Halogenated Heteropentalenes with One or Two Heteroatoms. Issue 9 (5th March 2013) - Chelucci, Giorgio; Baldino, Salvatore; Ruiu, Andrea
Abstract The mixture NaBH4/TMEDA promotes the Pd‐catalyzed hydrodehalogenation of brominated and chlorinated heteropentalenes under conditions A)‐C).